Noncollimating MmW polyethylene lens mitigating dual-source offset from a Tx/Rx WiGig module - Bisognin, A.; Titz, D.; Ferrero, F.; Jacquemod, G.; Pilard, R.; Gianesello, F.; Gloria, D.; Lugara, D.; Lima, E. B.; Costa, J. R.; Fernandes, C. A.; Luxe, C. (IEEE Transactions on Antennas and Propagation, 2015)
The design of a micromachined polyethylene lens for WiGig modules is described and its electromagnetic characteristics are measured. The lens is electromagnetically fed by linearly polarized Tx and Rx patch antennas integrated in an existing ball-grid-array (BGA) organic module. Antennas are separated from each other by a distance of 4.45 mm (0.89lambda at 60 GHz). The goal of the lens is to increase the gain of each antenna while lowering the beam depointing effect due to their offset position regarding the focal point of the lens. A geometrical optics/physical optics (GO/PO) hybrid method is applied to the design and analysis of the lens shape for noncollimating purpose. Using a lens height of 30 mm for both Tx and Rx antennas, a 13-dBi minimum realized gain from 54 to 66 GHz is obtained. Compared to an elliptical lens providing an equivalent realized gain over the same bandwidth, the depointing angle from the boresight direction is reduced from 15° to 4°. Full-wave simulations are verified by measurements.